X-Ray Images Processing to Detect Packaging Defects in Canned Food Industry Using Fuzzy Logic - Tafazoli, Marzieh (Journal of the University of Zulia, 2020)
Taking into account the importance of packaging in the food industry and the need to maintain the health of the materials in the packaging, and with the help of the experiences obtained from previous research with their strengths and weaknesses, we propose a method for the detection of defects in canned packaging, through the use of X-ray radiography, image processing and feature extraction methods, based on fuzzy logic functions for them.